2017
DOI: 10.4038/sljid.v7i2.8142
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a modified silver staining technique for detection of Leptospira

Abstract: Background: Leptospira are spiral thin and highly motile pathogenic bacteria that are best visualized by dark ground microscopy. Although these bacteria are not stained by the Gram's stain, the Fontana stain, which is a silver impregnation staining method, can be used successfully for light microscopy. It is important to investigate the usefulness of Fontana stain method for direct demonstration of Leptospirain human body fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Here, Leptospires were detected in urine smears stained by Fontana Method as long, thin, brownish black spirochaetes against yellow background. This is in agreement with previous studies by (Rodríguez et al, 2013;Gunasekara et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Here, Leptospires were detected in urine smears stained by Fontana Method as long, thin, brownish black spirochaetes against yellow background. This is in agreement with previous studies by (Rodríguez et al, 2013;Gunasekara et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…These results indicated that, the Fontana Method is an easy, rapid and cost effective test for detection of Leptospires in cattle and dogs' urine, which can be used in laboratories, where DFM is unavailable (Yesilmen et al, 2012;Gunasekara et al, 2017). Fontana Method has higher sensitivity when compared with DFM (Rodríguez et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A variety of histopathological stains are used for the detection of leptospires in clinical specimens. Although silver stains have been documented to be of use in the literature [ 212 ], the Warthin-Starry stain is widely in use now. Azizi et al [ 213 ] commented that histopathological stains (including Warthin-Starry stain) can sometimes confer false negative results, as the leptospirosis burden in tissue biopsies (such as kidneys) may not be significant.…”
Section: Diagnosis Of Leptospirosismentioning
confidence: 99%